2022
DOI: 10.1101/2022.03.07.483267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community structure determines the predictability of population collapse

Abstract: Early warning signals (EWS) are phenomenological tools that have been proposed as predictors of the collapse of biological systems. Whilst a growing body of work has shown the utility of EWS based on either statistic derived from abundance data or shifts in phenotypic traits such as body size, so far this work has largely focused on single species populations.However, in order to predict reliably the future state of ecological systems which inherently could consist of multiple species, understanding how reliab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…For example, whereas the linearized dynamics can be used to compute a recovery rate under equilibrium (Arnoldi et al ., 2018, Medeiros et al ., 2021, Strogatz, 2018), we show that they can be used to derive the time-varying expected sensitivity of different species to perturbations under non-equilibrium dynamics. Similarly to previous studies, our results confirm the utility of tracking variances and covariances of perturbed abundances to anticipate changes in ecological communities (Baruah et al ., 2022, Chen et al ., 2019, Dakos, 2018). In addition, we use the leading eigenvector, which has been previously employed to decompose community responses into species responses to perturbations under equilibrium dynamics (Dakos, 2018, Ghadami et al ., 2020, Patterson et al ., 2021, Weinans et al ., 2019).…”
Section: Discussionsupporting
confidence: 90%
“…For example, whereas the linearized dynamics can be used to compute a recovery rate under equilibrium (Arnoldi et al ., 2018, Medeiros et al ., 2021, Strogatz, 2018), we show that they can be used to derive the time-varying expected sensitivity of different species to perturbations under non-equilibrium dynamics. Similarly to previous studies, our results confirm the utility of tracking variances and covariances of perturbed abundances to anticipate changes in ecological communities (Baruah et al ., 2022, Chen et al ., 2019, Dakos, 2018). In addition, we use the leading eigenvector, which has been previously employed to decompose community responses into species responses to perturbations under equilibrium dynamics (Dakos, 2018, Ghadami et al ., 2020, Patterson et al ., 2021, Weinans et al ., 2019).…”
Section: Discussionsupporting
confidence: 90%
“…When an ecological network collapses both at the local as well as at the spatial scale, signals of global meta-network instability could also be manifested in species in an ecological community. It is relatively unknown, however, which species could exhibit signals of instability, but see Dakos (2017) , Baruah et al (2022) or Patterson et al (2021). Indeed, the species that exhibited strong increases in standard deviation as networks collapsed, were the ones which had on average a larger number of interactions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that in addition to monitoring dynamics of species abundance, phenotypic traits should be monitored as well. Including information from phenotypic dynamics such as body size could improve forecasts of biodiversity collapse (Clements and Ozgul 2016), although such an accurate forecast of biodiversity collapse is dependent on the type of environmental perturbation and the type of interactions prevalent in the community (Baruah et al 2019(Baruah et al , 2022. When changes in the environment impact communities both locally and spatially alike, ecological networks could abruptly collapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations